Assessing the extent of individual's creativity: pilot assessment - Mat Nawi, Nur Ainatul Mardiah; Hamidon, Huda; Md Radzi, Salliza; Mohamad Rosman, Mohamad Rahimi; Md Arifin, Noor Arina; Mokhtar, Siti Aishah (Faculty of Information Management, 2025)
Individual creativity plays a vital role in how the individuals approach and solve problems. The purpose of this pilot study is to investigate the relation between organizational culture and individual creativity in higher education institutions. The study is adopting quantitative research methodology. 30 academics completed on the online survey which consist of 6 sections. The research framework is based on four organizational culture that include adhocracy, market, clan, and hierarchy. In the study all four cultural dimensions have been reported to positively impact individual creativity. Cronbach alpha coefficients further supported the reliability coefficient of the instrument. One of the identified indicators, which is managing coordination is discovered to be unreliable as it resulted to a coefficient of 0.28. Thus, the item is omitted from the study. The findings of the study explore on the effect of organizational culture on individual creative behavior and its implications for higher learning institutions. It is recommended that more respondents should be included in future research study and future research should look at creativity in a variety of organizational settings.